2016
DOI: 10.2134/jeq2015.10.0529
|View full text |Cite
|
Sign up to set email alerts
|

Standard Extraction Methods May Underestimate Nitrate Stocks Captured by Field‐Aged Biochar

Abstract: Biochar (BC) has been shown to increase the potential for N retention in agricultural soils. However, the form of N retained and its strength of retention are poorly understood. Here, we examined if the N retained could be readily extractable by standard methods and if the amount of N retained varied with BC field ageing. We investigated soil and field-aged BC (BC) particles of a field experiment (sandy soil amended with BC at 0, 15, and 30 t ha) under two watering regimes (irrigated and rain-fed). Throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 77 publications
7
70
0
Order By: Relevance
“…The findings of this study are consistent with the results of other biochar researches carried out under controlled laboratory-based conditions (Mizuta et al, 2004;Yao et al, 2012;Liang et al, 2014), which observed some nitrate adsorption with some high temperature biochars. They are also in line with the results of a field experiment recently reported by Haider et al (2016). The authors observed that on a cultivated temperate sandy soil biochar reduced nitrate leaching.…”
Section: Resultssupporting
confidence: 91%
“…The findings of this study are consistent with the results of other biochar researches carried out under controlled laboratory-based conditions (Mizuta et al, 2004;Yao et al, 2012;Liang et al, 2014), which observed some nitrate adsorption with some high temperature biochars. They are also in line with the results of a field experiment recently reported by Haider et al (2016). The authors observed that on a cultivated temperate sandy soil biochar reduced nitrate leaching.…”
Section: Resultssupporting
confidence: 91%
“…Similarly, 313 ± 5.77 mg NH 4 + kg -1 biochar and 120 mg NH 4 + kg -1 biochar was observed for hot nutrient-enriched biochar to be added at 1% and 4% dosages, respectively (Table B in S1 File). These N min contents were likely underestimated as only one singular KCl extraction was done while Kammann et al [29] and Haider et al [39] have recently demonstrated that serial KCl extractions of biochar may lead to significant higher N min quantities captured by biochar. Total N contents for hot nutrient-enriched biochar were 4.3% and 2.5%, respectively, for the biochar to be added at 1% and 4% dosages.…”
Section: Resultsmentioning
confidence: 99%
“…Biochar nutrients capture increased plant growth considerably when such composted biochar particles were used as soil amendment, compared with the same but untreated, pristine biochar (Kammann et al , ). Some studies reported reduced N (nitrate) leaching (Major et al , ; Ventura et al , ; Haider et al , ) when biochar was applied to soil combined with mineral or organic N fertilizer.…”
Section: Introductionmentioning
confidence: 99%